2014
DOI: 10.1165/rcmb.2013-0008oc
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Contribution of Epithelial Damage to Airway Remodeling. Novel Therapeutic Targets for Asthma

Abstract: It has been suggested that an inherent airway epithelial repair defect is the root cause of airway remodeling in asthma. However, the relationship between airway epithelial injury and repair, airway remodeling, and airway hyperresponsiveness (AHR) has not been directly examined. We investigated the contribution of epithelial damage and repair to the development of airway remodeling and AHR using a validated naphthalene (NA)-induced murine model of airway injury. In addition, we examined the endogenous versus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
4
30
0
1
Order By: Relevance
“…There was a significant increase in AHR in OVA-sensitized/challenged mice compared with that measured from saline-sensitized/challenged controls (Po0.05 vs saline group). In contrast, there was no significant difference in airway reactivity between NA-treated and CO-treated mice, consistent with previous studies 23 and reflecting the fact that NA-treated mice undergo reparative healing by 3 days post injury, which is not associated with increased AHR. In comparison, only OVA þ NA-treated mice exhibited significantly enhanced AHR compared with that measured from OVA-sensitized/challenged (Po0.05 vs OVA group) and NA-treated mice (Po0.001 vs NA group; Figure 5).…”
Section: Total Lung Collagen Concentrationsupporting
confidence: 90%
See 4 more Smart Citations
“…There was a significant increase in AHR in OVA-sensitized/challenged mice compared with that measured from saline-sensitized/challenged controls (Po0.05 vs saline group). In contrast, there was no significant difference in airway reactivity between NA-treated and CO-treated mice, consistent with previous studies 23 and reflecting the fact that NA-treated mice undergo reparative healing by 3 days post injury, which is not associated with increased AHR. In comparison, only OVA þ NA-treated mice exhibited significantly enhanced AHR compared with that measured from OVA-sensitized/challenged (Po0.05 vs OVA group) and NA-treated mice (Po0.001 vs NA group; Figure 5).…”
Section: Total Lung Collagen Concentrationsupporting
confidence: 90%
“…Characterization of a novel model of asthma SG Royce et al repair peptide, trefoil factor 2, 23,25 it can be suggested that epithelial damage alone can lead to subepithelial airway fibrosis (as demonstrated by the increased NA-induced subepithelial collagen thickness and total lung collagen concentration), similar to processes occurring in human asthma where repeated episodes of epithelial injury lead to prolonged activation of the epithelial mesenchymal trophic unit. 26,27 Previous studies have shown that epithelial damage results in epithelial cells releasing pro-inflammatory factors such as IL-1 and tumor necrosis factor-a.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations